STRATEGI PENERAPAN PEMBELAJARAN AREA DALAM MEMBENTUK KARAKTER PESERTA DIDIK ANAK USIA DINI - Lestari, Anastasia Yani; Lawa, Petroila Trivena Imelda; Dau, Yoseph Lodowik Deki (Sekolah Tinggi Pastoral St. Petrus Keuskupan Atambua, 2022)
This literature research aims to investigate strategies for implementing area learning in shaping the character of early childhood students. Character formation in early childhood has a significant long-term impact on the formation of individuals who are strong and responsible in society. Therefore, understanding effective learning strategies in this context is essential. This library research combines text sources related to strategies for implementing area learning and character formation in early childhood. Data were analyzed through content analysis methods to identify key findings and trends in relevant literature. The findings from this literature research reveal that the application of area learning has a significant role in shaping the character of early childhood students. Some effective strategies in achieving this goal include the use of diverse and interesting learning environments, a values-based approach, and the active role of educators in providing positive examples. Apart from that, collaboration between teachers, parents and the community also emerges as a key factor in forming the character of young children.